2020
DOI: 10.1080/10691898.2020.1720552
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Undergraduates to Concepts of Survey Data Analysis

Abstract: Increasingly students, particularly those in the social sciences, work with survey data collected through a more complex sampling method than a simple random sample. Failing to understand how to properly approach survey data can lead to inaccurate results. In this article, we describe a series of online data visualization applications and corresponding student lab activities designed to help students and teachers of statistics better understand survey design and analysis. The introductory and advanced material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…In this study, we could not observe the application of the Chi-square statistic with the continuity correction factor. This situation is similar to other studies that propose activities to work the Chi-square tests with students [61][62][63][64]. For example, Gibbs and Goossens [64] talk about the relevance of the continuity correction factor and that it is usually not used when working with software because some (e.g., Minitab) do not have the option to use this factor.…”
Section: Final Reflectionssupporting
confidence: 67%
“…In this study, we could not observe the application of the Chi-square statistic with the continuity correction factor. This situation is similar to other studies that propose activities to work the Chi-square tests with students [61][62][63][64]. For example, Gibbs and Goossens [64] talk about the relevance of the continuity correction factor and that it is usually not used when working with software because some (e.g., Minitab) do not have the option to use this factor.…”
Section: Final Reflectionssupporting
confidence: 67%
“…The analytic procedures accounted for the stratification and produced proper variance estimates. 16 Data are presented as means or proportions with associated 95% confidence intervals (CIs). Confidence intervals are reported to help the reader consider situational relevance; for example, small overlaps of CIs might be significant with a larger sample.…”
Section: Methodsmentioning
confidence: 99%
“…In this sense, diverse authors (e.g., Woodard et al 2020;Fellers and Kuiper 2020;DePaolo et al 2016;Seier 2014;Gibbs and Goossens 2013;Leigh and Dowling 2010), have reported activities or problems proposals with the finality to make more accessible the study of the 2 tests, goodness-of-fit, independence, and homogeneity, which correspond to the problem areas presented in the previous section. However, commonly, in these investigations, the last partial meanings of each problem area (i.e., PM3, PM7 y PM11) were used.…”
Section: Incidence Of Partial Meanings Identified For the Statistical Education Researchmentioning
confidence: 99%